2012
DOI: 10.1007/s10048-011-0312-7
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation that Xq27 and Xq28 are susceptibility loci for migraine in independent pedigrees and a case-control cohort

Abstract: Investigations into migraine genetics have suggested that susceptibility loci exist on the X chromosome. These reports are supported by evidence that demonstrates male probands as having a higher proportion of affected first-degree relatives as well as the female preponderance of 3:1 that the disorder displays. We have previously implicated the Xq24-28 locus in migraine using two independent multigenerational Australian pedigrees that demonstrated excess allele sharing at the Xq24, Xq27 and Xq28 loci. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It is worth noting that in addition to HPCX1, other disease-associated loci were mapped to Xq27-q28, including the TGCT locus linked to hereditary testicular cancer and the susceptibility loci for dyslexia, autism and migraine (Lutke et al 2004; de Kovel et al 2004; Slavotinek et al 2005; Vincent et al 2005; Maher et al 2012). Therefore, the study of newly identified coding regions in a series of these disorders would be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that in addition to HPCX1, other disease-associated loci were mapped to Xq27-q28, including the TGCT locus linked to hereditary testicular cancer and the susceptibility loci for dyslexia, autism and migraine (Lutke et al 2004; de Kovel et al 2004; Slavotinek et al 2005; Vincent et al 2005; Maher et al 2012). Therefore, the study of newly identified coding regions in a series of these disorders would be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The female preponderance of migraine suggests the disease is partly influenced by X-linked genomic factors. To date migraine susceptibility loci have been convincingly mapped to Xq24–28 and suggestively mapped to Xp22, mainly via pedigree linkage studies [8] , [9] , [10] , [11] . For complex disease such as migraine the interplay between multiple genetic factors can make it difficult to distinguish the role each factor plays in the pathophysiology of disease.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed the X chromosomal data from a recent genome-wide association study [7] using a two-step method. We decided to separate the X chromosome from the autosomal analysis due to the specific X-linked hypothesis being tested and our previous findings regarding X chromosome loci and migraine [8] , [9] , [10] . Step one involved a preliminary scan of the data using a logistic regression association study approach controlling for age and gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of migraine as an X‐linked disorder is suggested by the female preponderance of and evidence that a high proportion of affected males have a greater number of affected first‐degree relatives . In a linkage analysis of 6 migraine pedigrees and a case–control cohort study that evaluated 11 candidate genes, 2 distinct susceptibility variants were identified at Xq27 (marked by DXS8043—DXS297) and Xq28 (DXS8061—XqTer) . Because these susceptibility regions were also associated in the case–control population, the possibility was raised that these loci are not pedigree‐specific and may be contributing to migraine in the general population.…”
Section: Genes For Common Migraine Subtypesmentioning
confidence: 99%